2021
DOI: 10.1177/14644207211060465
|View full text |Cite
|
Sign up to set email alerts
|

On comparison of recycled LDPE and LDPE–bakelite composite based 3D printed patch antenna

Abstract: In the past two decades number of studies have been reported on the use of thermoplastics as a substrate for 3D printed patch antennas. However, no work has been reported on the thermoplastic-thermosetting composite-based substrate for 3D printed patch antennas and their mechanical, morphological, rheological, and radiofrequency (RF) characterization for sensing applications. In this study low-density polyethylene (LDPE) and LDPE-5% bakelite (BAK) composite-based patch antenna (resonating frequency 2.45 GHz) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The ε r and tan δ for substrate (TPU on CLW fiber) were calculated (Table 8) based on the reported literature. 44,45 The controlled variation in ε r of the substrate upon cyclic loading highlights its 4D property, as this results in programable RF output in the ISM band. It may be noted that for ensuring the reliability of the functional prototype, the samples were loaded and unloaded for two consecutive cycles (with 03 repetitions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ε r and tan δ for substrate (TPU on CLW fiber) were calculated (Table 8) based on the reported literature. 44,45 The controlled variation in ε r of the substrate upon cyclic loading highlights its 4D property, as this results in programable RF output in the ISM band. It may be noted that for ensuring the reliability of the functional prototype, the samples were loaded and unloaded for two consecutive cycles (with 03 repetitions).…”
Section: Resultsmentioning
confidence: 99%
“…18) ascertains the 4D characteristics of the substrate. The 𝜀 𝑟 and tan 𝛿 for substrate (TPU on CLW fiber) were calculated (Table 8) based on the reported literature [45,46]. The controlled variation in 𝜀 𝑟 of the substrate upon cyclic loading highlights its 4D property, as this results in programable RF output in the ISM band.…”
Section: Introductionmentioning
confidence: 99%
“…PVDF composite samples were further explored for their ε r , which was experimentally evaluated using an impedance analyzer (Figure 6). Based upon experimentally observed ε r values, ε eff was calculated using the standard set of equations 21 along with the different parameters of the ring resonator (to be employed as a sensor for smart implant) (Table 6). It may be noted that all dimensions of the ring resonator to be employed as a sensor have been calculated for resonating frequency of 2.45 × 10 9 Hz (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In the reported literature, several studies have been reported on non-absorbable implants, prepared with different metals/alloys, and composites [19][20][21] for various orthopedic applications. But yet little has been described on the partially absorbable smart implants of thermoplastic composites for online health monitoring of veterinary patients.…”
Section: Introductionmentioning
confidence: 99%
“…AM methods are being used in different industries including health and medicine, automotive, electronics, aerospace, food, construction, etc. (Singh et al , 2022a). Figure 1 shows a process flow for AM (Bozkurt and Karayel, 2021).…”
Section: Introductionmentioning
confidence: 99%